Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

(d) 8x + 3y = -4 5x + 2y = 6

Sagot :

We are given two equations involving x and y

[tex]\begin{gathered} 8x+3y=-4\text{ eq. 1} \\ 5x+2y=6\text{ eq. 2} \end{gathered}[/tex]

We want to solve these equations and find out the values of x and y.

We can use the substitution method to solve these equations.

[tex]\begin{gathered} 5x+2y=6 \\ 2y=6-5x \\ y=\frac{6-5x}{2}\text{ eq. 3} \end{gathered}[/tex]

Substitute eq. 3 into eq. 1 and then simplify.

[tex]\begin{gathered} 8x+3y=-4 \\ 8x+3(\frac{6-5x}{2})=-4 \\ 8x+\frac{18-15x}{2}=-4 \\ \frac{2(8x)+18-15x}{2}=-4 \\ 16x+18-15x=-8 \\ 16x-15x=-8-18 \\ x=-26 \end{gathered}[/tex]

So we have found the value of x.

Now substitute the value of x into eq. 3 to get the value of y.

[tex]\begin{gathered} y=\frac{6-5x}{2} \\ y=\frac{6-5(-26)}{2} \\ y=\frac{6+130}{2} \\ y=\frac{136}{2} \\ y=68 \end{gathered}[/tex]

So we have found the value of y.

Therefore, the solution is

[tex]\begin{gathered} x=-26 \\ y=68 \end{gathered}[/tex]